SISTEM PENGANTRIAN MEJA PADA RESTORAN DENGAN FASILITAS SMS - Suryati, Indra; Nurwijayanti, Nurwijayanti; Hakim, Christa Usteng (TESLA Jurnal Teknik Elektro UNTAR, 2008)
Nowadays, the developers of restaurant are going fast with more kind of dish which comes from Indonesia although from outer Indonesia such as Chinese, Japanese and American food. With a lot of kind of dish, its make people have an interest to try. This matter makes people willing to waiting in a list for eat their favourite food. The data processing still do manually. The design of the table queue instrument which use the SMS facilities include the maker of restaurant map simulation, LED used for the sign of present or unpresent of customer and software that useful for the SMS sending process and run the simulation. These designs are made for easier the receptionist job and make customer more comfort in a queue process